2017
DOI: 10.1155/2017/4873459
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Resource Utilization Prediction System for Infrastructure as a Service Cloud

Abstract: Infrastructure as a Service (IaaS) cloud provides resources as a service from a pool of compute, network, and storage resources. Cloud providers can manage their resource usage by knowing future usage demand from the current and past usage patterns of resources. Resource usage prediction is of great importance for dynamic scaling of cloud resources to achieve efficiency in terms of cost and energy consumption while keeping quality of service. The purpose of this paper is to present a real-time resource usage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Datacenter resource prediction using neural networks ANN is a suitable method of prediction in our case because we have shown that it data has a non-Gaussian distribution. It has also shown good performance than other prediction models [29,38]. Moreover, ANN has a great ability to model a non-linear function thus able to handle complex time series [39,48,49].…”
Section: Algorithm 2: Finding the Number Of Vm Peaks That Occur Simulmentioning
confidence: 99%
See 2 more Smart Citations
“…Datacenter resource prediction using neural networks ANN is a suitable method of prediction in our case because we have shown that it data has a non-Gaussian distribution. It has also shown good performance than other prediction models [29,38]. Moreover, ANN has a great ability to model a non-linear function thus able to handle complex time series [39,48,49].…”
Section: Algorithm 2: Finding the Number Of Vm Peaks That Occur Simulmentioning
confidence: 99%
“…Efficient management of power usage in data centres through prediction and VM sizing is on the rise [11,28,29]. However, the approaches used have not attempted to combine VM sizing and resource usage prediction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Load balancing at the IaaS level can be effectively done by predicting the future resource requirements of the new tasks and allocating the resources at the physical machine accordingly [24]. Based on the predicted load the set of physical machines is sorted in descending order.…”
Section: Optimal Vm Allocation Frameworkmentioning
confidence: 99%
“…There could also be delay introduced due to VM provisioning and deprovisioning. IaaS cloud resources can be effectively utilized by predicting the future workload or the future resource utilization pattern [8].…”
Section: Introductionmentioning
confidence: 99%